MAC Layer Communication Protocol design using Stochastic Network Calculusfor Underwater Agriculture Farming - MR Christhuraj, Manikandan TT, Saravanan M, Rajeev Sukumaran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: The hazardous in seawater network, channel utilization, and MAC layer protocol design induces the research challenges and opportunities of underwater acoustic communications, particularly in terms of throughput and transmission delay. In this research work, we propose the delay-tolerant MAC protocol with collision avoidance. Under_Water Medium Access control and Collision Avoidance -Wireless protocol (UWMACA-W) proposed for underwater Agriculture Farming. This research work also has compared the performance of the UWMACA-Wireless protocol with and without SNC. The growth of the plants inside the bubble can be exchanged to the base station by using the UWMACA-wireless protocol and also increases interface efficiency by taking account of the underwater acoustic channel's long delay time, as well as fixing the issues related to uncovered terminal issues. UWMACA-W method has higher performance than MACA-Wireless protocol, according to simulation testing on Riverbed modeler.